Handling the pharmaceutical industry waste in Ukraine and the UA - Popovych, Olena; Vronska, Nataliya; Yatchyshyn, Yuriy; Zaharko, Yaroslava (Видавництво Львівської політехніки, 2020)
The prospects of the pharmaceutical industry development are closely connected with scientific and technological progress. In Ukraine, handling hazardous medical waste is an open question. The rapid development of pharmacy in recent years has created and increased the possibility of the generation and accumulation of pharmaceutical waste at the enterprises and in the environment. Only a few enterprises deal with medical waste disposal. Medical waste recycling requires an extremely high level of attention and carries great risks associated with handling this medical waste. When medical waste is burnt, strong pollutants are released into the atmosphere – carcinogens, furans and dioxins from chlorine halogen compounds, namely dumping of the hazardous material that contains heavy metals, and is likely to cause bioaccumulative hazardous substances to transfer to the environment.
Keywords: medical and pharmaceutical waste; medicines; concentration; purification; methods; packaging; disposal; processing